Chemical and Biological Investigations of Axonopus compressus (Sw.) P. Beauv. - Rahman, FM Mustafizur; Kabir, SM Fuad; Nurnabi, Md; Chowdhury, AM Sarwaruddin; Sikder, Md Al Amin (Bangladesh Pharmaceutical Journal, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/bpj.v17i1.22345 Bangladesh Pharmaceutical Journal 17(1): 113-115, 2014